2021
DOI: 10.1177/09603271211006167
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of 19 amino acids in triptolide-induced liver injured rats by gas chromatography-triple quadrupole mass spectrometry

Abstract: The liver is an important organ for amino acid metabolism, and its damage can be reflected in the changes of amino acid level in the body. Triptolide (TP) has broad anti-inflammatory and anti-tumor activities, but its clinical application is limited due to hepatotoxicity. In this work, a simple, accurate and sensitive gas chromatography-triple quadrupole mass spectrometry (GC-QqQ-MS/MS) method was developed and validated for evaluating the serum levels of amino acids from control and TP-induced liver injured r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Indole-3-acetate, closely associated with Bifidobacterium and Bacteroides [39] , requires further investigation to understand its relationship with inflammation or liver injury. The liver's vital role in amino acid metabolism influences various diseases, including liver injury, cardiovascular disease, and diabetes [40][41][42] . Gly is an amino acid that benefits the liver by protecting liver cells and reducing damage [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Indole-3-acetate, closely associated with Bifidobacterium and Bacteroides [39] , requires further investigation to understand its relationship with inflammation or liver injury. The liver's vital role in amino acid metabolism influences various diseases, including liver injury, cardiovascular disease, and diabetes [40][41][42] . Gly is an amino acid that benefits the liver by protecting liver cells and reducing damage [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In general, tryptophan has three metabolic pathways, namely the Kynurenine pathway, the 5-hydroxytryptamine pathway, and the indole pathway. Existing studies have confirmed that tryptophan has many biological activities, such as regulating growth, regulating immunity, and anti-oxidative stress [ 38 , 39 ]. In the liver, tryptophan is involved in the synthesis of proteins, and when a toxic injury occurs in the liver, the serum tryptophan level decreases, which in turn promotes the release of pro-inflammatory cytokines and apoptosis, exacerbating hepatic inflammatory response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pentose and glucuronate interconversions, alanine, aspartate and glutamate metabolisms, and arginine and proline metabolisms were the common pathways in the lowdose and high-dose groups. Alanine, aspartate, and glutamate metabolisms were both time-and dose-related pathways, which have been proved to be closely related to the mechanism of drug toxicity according to Hu et al (2021a).…”
Section: Metabolic Pathway Analysis Of Urine Metabolitesmentioning
confidence: 99%